Governing the (Dis)Order: Toke and the Convergence of Artisanal Oil Mining and State Visibility in Sumur Baru - Sununianti, Vieronica Varbi; Sujito, Arie; Nugroho, Heru (Forest and Society, 2024)
This article explores the question of why and how ‘illegal’ artisanal mining in the oil-rich region of Indonesia remains in place despite official bans by the central government. By taking a qualitative ethnographic study on the practice in Sumur Baru, Dusun Tue, a village in South Sumatra Province, our inquiry takes seriously the formation of resilient labor in daily encounters with state institutions. We employ a governmentality approach and show how quotidian interactions between state and community has legitimized practices of artisanal mining. Sites become relatively governable in conditions of continuous displacement through ongoing negotiations between intermediaries (Toke) with state agencies. This practice is made possible by the use of Sen Minyak or oil money that binds Toke as key representatives of the community with police and state apparatuses as disciplinary representatives of the governmental state. This study thus shows how an extractive regime emerges, shifts, and reshapes in the local political economic contexts of Indonesia’s decentralization era.